Measurement of the branching fraction of the B0→D+sπ− decay; The European Physical Journal C; Vol. 81, iss. 4 - Aaij R. Roel; Beteta C. B. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen